ABO non‐O type as a risk factor for thrombosis in patients with pancreatic cancer. (15th August 2015) - Li, Donghui; Pise, Mayurika N.; Overman, Michael J.; Liu, Chang; Tang, Hongwei; Vadhan‐Raj, Saroj; Abbruzzese, James L.
Abstract : ABO non‐O type is associated with the risk of thrombosis in pancreatic cancer patients. Tumor site, antithrombotic medication, and obesity are associated with thrombosis. Early thrombosis event conferred a significantly higher risk of death. Abstract: ABO blood type has previously been identified as a risk factor for thrombosis and pancreatic cancer (PC). The aim of the study is to demonstrate the associations between ABO blood type and other clinical factors with the risk of thromboembolism (TE) in patients with PC. We conducted a retrospective study in 670 patients with pathologically confirmed pancreatic adenocarcinoma at the University of Texas MD Anderson Cancer Center. Clinical information was retrieved from medical records. ABO blood type was determined serologically and/or genetically. Logistic regression models, Kaplan–Meier plot, log‐rank test, and Cox proportional hazard regression models were employed in data analysis. The incidence of TE was 35.2% in 670 patients who did not have TE prior to cancer diagnosis. Pulmonary embolism (PE) and deep vein thrombosis (DVT) consisted 44.1% of the TE events. Non‐O blood type, pancreatic body/tail tumors, previous use of antithrombotic medication, and obesity (body mass index >30 kg/m 2 ) were significant predictors for TE in general. Blood type A and AB, low hemoglobin level (≤10 g/dL), obesity, metastatic tumor, and pancreatic body/tail tumors were significant predictors for PE and DVT. Patients with metastatic tumor or pancreatic body/tail tumors had a much higher frequency of early TE events (≤3 months after cancer diagnosis); and early TE occurrence was a significant independent predictor for increased risk of death. These observations suggest that ABO non‐O blood type is an independent predictor for TE in PC. A better understanding of the risk factors for TE in PC may help to identify patients who are most likely to benefit from prophylactic anticoagulation therapy.